GAMBARAN FAKTOR-FAKTOR YANG MELATARBELAKANGI MASYARAKAT MELAKUKAN VAKSINASI COVID-19 DI WILAYAH KERJA PUSKESMAS RUMBAI BUKIT - Dwi Oktiviani; Arneliwati Arneliwati; Herlina Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Attempts to prevent the spread of the Covid-19 virus are to carry out vaccines. Vaccines are useful for forming a person's immune system in order to break the chain of transmission of the Covid-19 virus. The purpose of this study is to investigate the factors that influence people to carry out the Covid-19 vaccination. This study used a simple descriptive. This research was conducted at the Rumbai Bukit Public Health Center Pekanbaru City, with 98 samples taken using purposive sampling technique and paying attention to the inclusion criteria. The measuring instrument is a questionnaire that has been tested for validity and reliability. Additionally, the analysis that was applied in this research was a univariate analysis. In this study, the sex distribution was mostly female, amounting to 53 respondents (54.1%), most of the respondents were aged 19-40 years / early adulthood, which was 62 respondents (63.3%). While the level of education mostly is senior high schoo studentl/equivalent with 54 respondents (55.1%). Therefore, housewives were the most likely to get vaccinated with amounted to 35 respondents (35.7%). The results of the study on the level of public knowledge about Covid-19 vaccination were 67 respondents (68.4%) with good knowledge. And while for the level of public perception of the Covid-19 vaccination is 61 respondents (62.2%) have a positive perception. Based on the results of this study, the researchers concluded that the general public has good knowledge and positive perceptions so that from these factors it help incourage people to carry out Covid-19 vaccinations. Keywords: Covid-19, Knowledge, Perception, Vaccine